Perilaku Makan Remaja Putri Anemia dan Tidak Anemia di SMA Negeri Kota Kendal - Mursiti, Titi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTAccording to the Health Research (Riskesdas) in 2013 estimated prevalence of anemia in Indonesia â‰¥ 20%. naemia in adolescent girls one of which is caused by poor eating behaviors such as restriction of food intake, vegetarian diet and others - others. The purpose of this study was to analyze the factors that influence eating behavior of young women anemia and anemia in SMA Kendal. This research is an observational cross-sectional quantitative approach. The population in this study were all high school student Affairs at Kendal Town, sampling technique in this study Using proportionate stratified random sampling in 91 respondents. The results showed the Young Women who are anemic as much as 25.6%, Behavior eat as much as 44.4 % less good, less good knowledge as much as 65.6 %. Young women whose attitude toward good nutritional needs as much as 55.6%, which parents contribute as much as 58.9 %, which peers contribute as much as 63.3%, and the media play a young woman who is as much as 56.7 %. Feeding behavior of young women who are not anemic better than eating behavior of young women who are not anemic (p=0.035). Variables that are not associated with feeding behavior is the attitude of young women, the role of parents and the role of peers. This can be concluded that the feeding behavior of young women who are not anemic better than eating behavior of young women are anemic. Attitude ( OR 2.692 ) and the role of parents ( OR 3.746 ) effect together - at the feeding behavior of young women.Keywords: feeding behavior, young women, anemia